(untitled) (Global Journal of Science Frontier Research, 2020)
It is proved existence and uniqueness of solution of the problem with initial and boundary conditions of Maxwell-Auzhan (we consider pure specular reflection from the boundary) for the nonstationary nonlinear one-dimensional Boltzmann’s twelve-moment system equations in space of functions continuous in time and summable in square by spatial variable.